LHCII-assisted TiO2 photocatalysis of CO2 to small organic compounds - Antoniou Kourounioti, Rea Laila (2014)
CO2 photoreduction could be used to convert CO2 from the emissions of fossil-fuel power plants back into fuel using solar energy and photocatalysts such as TiO2. However, TiO2 absorbs UV light which is only a small portion of the solar radiation. Plants use the Light Harvesting Complex of photosystem II (LHCII) to maximise light absorption in photosynthesis. The work presented in this thesis investigates the combination of the LHCII and Rh-doped TiO2 photocatalyst, to increase the visible light absorption of the catalyst and improve its efficiency. LHCII was extracted from spinach leaves and adsorbed on to the TiO2:Rh catalyst surface. The presence of LHCII on the surface was confirmed by LHCII-specific peaks in absorption and fluorescence spectra. The performance of TiO2:Rh-LHCII was assessed in CO2 photoreduction with simultaneous water splitting. Methane, CO, methyl formate, acetaldehyde and hydrogen were detected in the reactor and the concentrations of all but CO, were greatly increased for TiO2:Rh-LHCII compared to TiO2:Rh in visible light experiments. Ordinary differential equation (ODE) models were developed for CO2 photoreduction to investigate the steady-state concentrations of the products and make predictions about their response to different experimental parameters. The light absorption was confirmed as a viable optimisation target for increasing product concentrations. A stochastic discrete spatial model was also developed which showed that spatial effects are important for reduction rates and that the hydrophilicity of the catalyst may lead to reaction stalling. It was concluded that, if issues with LHCII stability and maximising light absorption without interfering with catalysis are dealt with, LHCII could be a promising method for enhancing CO2 photoreduction with the appropriate catalyst.